Burden of Care: Management of Cleft Lip and Palate - Murthy, Jyotsna (Indian Journal of Plastic Surgery, 2019)
Burden of care has become a commonly used terminology in healthcare in the recent years. Burden of care is the balance how much patients and families commit to their time, compromise quality of life, undergo multiple interventions, and take risks weighing against the benefits the patients and families receive. Cleft lip and palate, congenital anomaly, demands a long-term and interdisciplinary care. These children are at high risk of various treatment/intervention episodes increasing the burden of care. This subject has been widely discussed with many other diseases and health conditions at national, international meetings, and World Health Organization as well. We bring out some facts and practices affecting the burden of care in cleft lip and palate.
Keywords: cleft lip and palate; burden of care; NAM; preoperative orthodontics procedures; cleft lip revision